The Influence of Financial Literacy and Financial Technology With Parental Guidance as a Moderating Variable on Saving Behavior of State University Students in Surabaya City - Sari, Anisa Kartika; Nur, Dhani Ichsanuddin; Khoirotunnisa, Fani (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Saving is very important for students to prepare for a more stable financial future. By saving, students can learn to manage finances, face urgent needs, and achieve long-term financial goals. This study aims to determine the effect of financial literacy and financial technology on saving behavior in state university students in Surabaya City and the role of parental guidance in strengthening or weakening the influence of financial literacy and financial technology on saving behavior in state university students in Surabaya City. This study uses quantitative methods and variable measurements using a Likert scale. Data were collected through questionnaires filled out by 100 respondents of state university students in Surabaya City using a purposive sampling technique. The data obtained were analyzed and tested using the Partial Least Square (PLS) method with SmartPLS 4. The results showed that financial literacy can contribute to saving behavior in state university students in Surabaya City. Financial technology can also contribute to saving behavior in state university students in Surabaya City. In addition, parental guidance is proven to be able to contribute to and strengthen the influence of financial technology on saving behavior on state university students in Surabaya City. However, parental guidance cannot contribute to and weaken the influence of the relationship between financial literacy and the saving behavior of state university students in Surabaya City.